A fundamental dual-zone continuum theory for dynamic soil-structure interaction. - Pak, Ronald Y. S.
A continuum theory for an improved characterization of dynamic soil structure interaction in the framework of three-dimensional elastodynamics is presented. Effective in demonstrating the importance of integrating free-field and near field effects under general soil and foundation conditions, a compact two-zone delineation of the soil medium is proposed as a quintessential mechanics perspective for this class of problems. Sufficient to deliver a practical resolution of some perennial analytical and experimental conflicts, a fundamental formulation commensurate to a gradated unification of the homogenization approach and any sole free field inhomogeneous representation is developed and implemented computationally. Specialized to the problem of a rigid circular footing on sand, a nominal set of dynamic contact stress distributions and related impedance functions by the dual zone theory is included for theoretical and engineering evaluation. Through its comparison with benchmark analytical solutions and relevant physical measurements, the usage of the underlying conceptual platform as an advanced yet practical foundation for general dynamic soil structure interaction is illustrated.
Keywords: Elasticity; Inhomogeneity; Structural dynamics; Soil dynamics; Soil structure interaction; Foundation; Sand; Impedance; Granular media; Contact problems; Wave propagation; Boundary element